Novas narrativas (Praxis Educativa, 2026)
We publish past and present works, and, drawing on the journal's historical trajectory, while resisting challenges in times of complexity and uncertainty, we share possible paths toward these "new futures" (Porta, 2026) for the field of education.
Keywords: narrativa; educação pública; território